2009
DOI: 10.1016/j.jep.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effect of Lafoensia pacari A. St.-Hil. ethanolic extract and fractions in mice

Abstract: These data indicate that the extract of Lafoensia pacari A. St.-Hil. possesses antidepressant-like properties in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 23 publications
0
38
0
3
Order By: Relevance
“…The number of ambulation (with at least three paws) and rearing (standing upright on hind paws), and the frequencies of grooming (including face cleaning, paw licking, fur licking, head scraping, and rubbing) were counted manually for 5 min as described in recent studies (Galdino et al, 2009;Tolardo et al, 2010). The apparatus was cleaned with 10% ethanol and dried thoroughly between tests.…”
Section: Open Field Testmentioning
confidence: 99%
“…The number of ambulation (with at least three paws) and rearing (standing upright on hind paws), and the frequencies of grooming (including face cleaning, paw licking, fur licking, head scraping, and rubbing) were counted manually for 5 min as described in recent studies (Galdino et al, 2009;Tolardo et al, 2010). The apparatus was cleaned with 10% ethanol and dried thoroughly between tests.…”
Section: Open Field Testmentioning
confidence: 99%
“…The phytochemical analysis of L. pacari stem bark revealed the presence of phenolic compounds, including flavonoids and tannins (Solon et al, 2000;Galdino et al, 2009). Previous studies have demonstrated that flavonoids and tannins have antioxidant activity, mainly due to their redox properties, absorbing or neutralizing free radicals that can attack biomolecules such as DNA (Degáspari and Waszczynskyj, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…St.-Hil., popularly known in Brazil as "pacari", "dedaleiro", "didal" and "mangabeira-brava", is a medicinal plant of the family Lythraceae that is widely used as an antipyretic, wound healing, anti-inflammatory, and antidiarrheal agent, as well as in the treatment of gastritis and cancer (Sampaio et al, 2011). Infusion or maceration in white wine or in water for oral administration are the most common methods for preparing a remedy with this plant (Solon et al, 2000;Galdino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations